2022
DOI: 10.1007/s40692-022-00220-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary four students’ perceptions towards self-directed learning and collaborative learning with technology in their English writing lessons

Abstract: The purpose of this study is to examine Primary school students’ perceptions towards self-directed learning (SDL) and Collaborative learning (CL) with and without the integration of Information and Communication Technologies (ICT) in English writing lessons in Singapore. There were 408 students participated in this study voluntarily. The results showed that the participants’ perceptions for SDL and CL were positive in both control and ICT-enhanced experimental groups, with means ranged from 3.73 to 3.90 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
4
1
Order By: Relevance
“…The inhibiting and renewal factors contribute in the same pattern to the composition of narrative texts, namely by making a direct contribution to the words and an indirect contribution to the words, sentences, and texts. This is based on the theory that the high-level executive function of planning can support the process of text production and reading comprehension (Choy & Cheung, 2022;Wubalem, 2021). However, the findings of this study are contrary to this theory, as there was no contribution found due to planning on any level of narrative text composition.…”
Section: Discussioncontrasting
confidence: 71%
“…The inhibiting and renewal factors contribute in the same pattern to the composition of narrative texts, namely by making a direct contribution to the words and an indirect contribution to the words, sentences, and texts. This is based on the theory that the high-level executive function of planning can support the process of text production and reading comprehension (Choy & Cheung, 2022;Wubalem, 2021). However, the findings of this study are contrary to this theory, as there was no contribution found due to planning on any level of narrative text composition.…”
Section: Discussioncontrasting
confidence: 71%
“…Hughes and Morrison [41]; Kim and Lee [32]; Alwadaeen and Piller [6]; Indrastyawati and Wu [44]; Choy and Cheung [54]; Labonté and Smith [51].…”
Section: Physical Environment and Technological Resourcesmentioning
confidence: 99%
“…This method seemed to be more effective than teacher-led discussions in class. Choy and Cheung [54] and Labonté and Smit [51] found that technologies used in the learning environment, such as tablets, online writing assistant tools and online notice boards, significantly increase school students' positive attitudes toward self-directed learning. As Hughes and Morrison [41] and Kim and Lee [32] argued, the physical space of a classroom is also important in the educational process; therefore, the conditions that enable a learner to move in their physical environment and communicate are as important as what materials and means they have.…”
Section: Hughes and Morrisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive impressions of ICT in the classroom and their influence on student success would, of course, be associated with the deployment of smartphone technology in the classroom (Fuchs, 2021a;Wilson et al, 2022). Educators that favor studentcentered learning, which places the emphasis on the student rather than the teacher, may be more likely to promote smartphone technology in the classroom since it allows for greater levels of self-directed learning (Choy and Cheung, 2022). Furthermore, teachers that favor inquiry-based learning, in which students must probe deeper into more open-ended issues, may be more amenable to introducing smartphone technology into the classroom (Deák et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%